2020
DOI: 10.1021/acs.jpcc.0c03244
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of TiOPc Films on Au(111): From Seed Layer to Crystalline Multilayers

Abstract: Since optoelectronic properties of organic semiconductor films are closely linked to their structural properties (such as molecular orientation, crystalline phase and orientation, degree of crystallinity, etc.), a microscopic understanding of heterogrowth behavior is of utmost importance to control and improve such films for device applications. For the case of titanyl phthalocyanine (TiOPc), a widely used molecular semiconductor for organic optoelectronics, the initial film growth on metal substrates has alre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…We found that such odd-layer islands were relatively rare and small compared to 2 and 4 ML regions, suggesting a strong preference for the bilayer motif. This alternating O-up/O-down order should result in a net cancellation of dipole moments, consistent with the bulk crystal phases of VOPc, and previous STM studies of other nonplanar MPcs. ,,,, …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…We found that such odd-layer islands were relatively rare and small compared to 2 and 4 ML regions, suggesting a strong preference for the bilayer motif. This alternating O-up/O-down order should result in a net cancellation of dipole moments, consistent with the bulk crystal phases of VOPc, and previous STM studies of other nonplanar MPcs. ,,,, …”
Section: Resultssupporting
confidence: 84%
“…This alternating O-up/ O-down order should result in a net cancellation of dipole moments, consistent with the bulk crystal phases of VOPc, 41 and previous STM studies of other nonplanar MPcs. 15,29,30,42,43 Compared to similar molecular systems, we find that the overall morphology in Figure 3 is more uniform. For example, deposition of >1 ML VOPc on either Ag(111) or Au(111) results in the formation of islands that are tilted with respect to the surface in addition to flat-lying films.…”
Section: The Journal Of Physical Chemistry Cmentioning
confidence: 75%
“…Despite these difficulties, RAIRS is particularly useful for the characterization of systems with low surface area, as well as to investigate adsorption of gas/solid and liquid/solid interfaces, 232,233 by providing accurate information on intermolecular interactions and additionally the bonding geometry of adsorbates. 234–243 Actually, the pioneering application of RAIRS was to investigate the adsorption of carbon monoxide on metal films. 244,245 The application of polarization modulation is also frequently used to improve the signal-to-noise ratio and to discriminate between adsorbed and free surrounding molecules.…”
Section: Surface Processesmentioning
confidence: 99%
“…In monolayer and few-layer heterostructures non-planar phthalocyanine molecules are most often oriented flat with their macrocycles parallel to the substrate plane. [16][17][18][19][20] Upon increasing the thickness and on non-metallic substrates the molecules tend to assume a 'standing-up' geometry. [21][22][23] In order to grow films with a flatter orientation of the molecular macrocycles it has been shown that suitable templating layers can be applied for this purpose.…”
Section: Introductionmentioning
confidence: 99%